2012
DOI: 10.1007/s00268-012-1835-2
|View full text |Cite
|
Sign up to set email alerts
|

Multifocality, But Not Bilaterality, Is a Predictor of Disease Recurrence/Persistence of Papillary Thyroid Carcinoma

Abstract: Although multifocal and bilateral PTC had aggressive pathologic features, only multifocality was associated with an increased risk of disease recurrence/persistence. This suggests that the number of tumor foci, but not their location, is a significant predictor of clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
105
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 37 publications
12
105
2
5
Order By: Relevance
“…In our study, all analyzed patients with MTMC were classified as unilateral tumors. The results of other studies showed that the clinicopathological characteristics did not differ between patients with multifocal-unilateral and multifocal-bilateral thyroid carcinomas [10]. It was confirmed, however, that multifocality and bilaterality are both connected with aggressive pathologic features.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In our study, all analyzed patients with MTMC were classified as unilateral tumors. The results of other studies showed that the clinicopathological characteristics did not differ between patients with multifocal-unilateral and multifocal-bilateral thyroid carcinomas [10]. It was confirmed, however, that multifocality and bilaterality are both connected with aggressive pathologic features.…”
Section: Discussionsupporting
confidence: 54%
“…Recent findings suggest that the incidence of recurrence or persistence was higher in patients with multifocality of TC compared to unifocal lesions, even if they underwent more aggressive treatment [10]. It might be suspected that this clinical scenario may be the consequence of the fact that patients with MTMC have higher rates of lymph node metastases, soft tissue invasion and distant metastases at the time of diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Хотя ряд авторов не без оснований полагают, что диаметр опухоли более 1 см сопряжен с повышением уровня агрессивности рака и риском местастазирования в лимфатические узлы шеи [3]. кроме того, доказано, что мультифокальный рост является фактором риска агрессивных форм рака, сопряженных с риском рецидива рЩж после операции [8].…”
Section: Introductionunclassified
“…However, some conditions such as extrathyroidal invasion, lymph node involvement, advanced stage, distant metastasis, and inadequate surgical therapy are related to high risk of recurrence and poor prognosis. In addition, multifocality or multicentricity is a frequent feature of these tumors, and is generally associated with advanced stage, increased risk of lymph node involvement, and the presence of distant metastasis, in comparison to solitary PTC [3,4]. In the literature, there are numerous studies comparing multifocal/bilateral and solitary PTCs; however, the risk factors affecting multifocality/multicentricity or bilaterality are not clear.…”
Section: Introductionmentioning
confidence: 99%